Analisis Pendekatan Konseling Narrative Therapy - Tasya Diandra Aulia; Puspita Sari, Rika; Okta Pratiwi; Dini Pramaessilla; Sigit Dwi Sucipto (Universitas PGRI Kanjuruhan Malang, 2023)
Narrative therapy is an approach or method used in the world of counseling that aims to invite counselors to tell stories and communicate experiences related to the problems they are experiencing. The focus of this approach is the most dominant narrative depiction of the council so that it is able to express the problems they encounter. The method used in this research is a library study with moreview 20 articles on narrative therapy counseling approaches that have been published and have been nationally accredited. The result of this research is that the approach of Narrative Therapy has been proven to be able to influence the solution of the problems that are being experienced.